Pelaksanaan Informed Consent Dalam Pelayanan Medik - Adi Rizka; Cut Khairunnisa; Zikra Ihtasya Annabila; Santri Windiani (Universitas Malahayati Lampung, 2023)
ABSTRACT Informed consent is a rule that every medical action must obtain the consent of the patient or the patient's family. However, before the approval is given, the doctor has the obligation to provide comprehensive information about the patient's illness, the type of medical action to be carried out, the chances of recovery, the risks of medical action, and the costs required to carry out the treatment. In addition, doctors must also provide opportunities for patients to have a second opinion with another doctor and provide alternative treatments other than what the doctor has suggested. After the doctor provides this information, the patient can decide to accept or reject the medical treatment suggested by the doctor. Informed consent is an embodiment of caution in carrying out medical procedures so that doctors and patients already have an overview of the success or failure of medical action before surgery or medical treatment is carried out. Another benefit, in the aspect of law enforcement, informed consent can be used as evidence in court if there is a lawsuit from either the doctor or the patient, or the patient's family. Keywords: Services, Informed Consent, Medical Services ABSTRAK Informed consent merupakan suatu aturan dimana setiap tindakan medik harus mendapatkan persetujuan dari pasien atau keluarga pasien. Namun, sebelum persetujuan itu diberikan, dokter mempunyai kewajiban untuk memberikan informasi secara menyeluruh tentang penyakit yang diderita pasien, jenis tindakan medik yang akan dijalankan, peluang kesembuhan, resiko tindakan medik dan biaya yang dibutuhkan dalam menjalankan perawatan tersebut. Selain itu, dokter juga harus memberikan peluang kepada pasien untuk melakukan second opinion dengan dokter lain dan memberikan alternatif pengobatan selain daripada yang sudah disarankan dokter bersangkutan. Setelah dokter memberikan informasi tersebut, pasien dapat memutuskan menerima atau menolak tindakan medik yang disarankan dokter tersebut. Informed consent merupakan perwujudan daripada sikap kehati-hatian dalam menjalankan tindakan medik sehingga dokter dengan pasien sudah mempunyai gambaran keberhasilan atau kegagalan daripada tindakan medik sebelum operasi atau rawatan medik dilakukan. Manfaat lainnya, dalam aspek penegakkan hukum, informed consent dapat dijadikan alat bukti di pengadilan sekiranya ada tuntutan hukum baik dari pihak dokter maupun pasien atau keluarga pasien. Kata Kunci: Pelayanan, Informed Concent, Pelayanan Medik